Assessment of body metrics, weight, and carcass yields in dusky grouper (Epinephelus marginatus) through correlation and path analysis: Implications for optimizing genetic breeding programs - Tarôco, Graziela; Perazza, Caio Augusto; Gomes, Maria Emília de Souza; Kerber, Claudia Ehlers; Reis-Neto, Rafael Vilhena [UNESP]; Hilsdorf, Alexandre Wagner Silva (Elsevier, 2024)
One of the objectives of aquaculture selective breeding programs is to enhance body conformation traits, often by using indirect criteria like correlation between live body measurements and carcass traits. This research investigated the relationship between live body measurements and carcass traits in dusky grouper (Epinephelus marginatus). We assessed the relationship between body measurements and carcass traits in 150 farmed dusky groupers with an average weight of 680 ± 221 g. The fish were measured for length, width, height, and length of head, and then processed to obtain weights (body, fillet, steaks, head, and residues) and yields (carcass, fillet, steaks, head, and residues). Path analysis was employed to estimate direct and indirect effects, with body part weight and yields as dependent variables and morphometric measurements and relationships as explanatory variables. The findings indicate that morphometric measurements can be used to estimate farmed dusky grouper body weights and carcass yields. Among the morphometric measurements and relationships examined, fish body height and standard length were identified as the main factors influencing variation in body weights and carcass yields.
Keywords: Animal breeding; Direct and indirect effect; Marine fish; Multivariate analysis; Phenotypic correlation